The healing goddess Gula : towards an understanding of ancient babylonian medicine - Böck, Barbara (Barbara Alexandra) (Culture and history of the ancient Near East, 2014)
Providing a comprehensive study of the Ancient Babylonian healing goddess, this book employs a range of Sumero-Akkadian cuneiform sources. The resulting volume challenges many long-held assumptions concerning the specialized medical literature and addresses the nature of healing in Ancient Mesopotamia.